A Value Chain Approach to Characterize the Chicken Sub-sector in Pakistan - Aslam, Hassaan Bin; Alarcon, Pablo; Yaqub, Tahir; Iqbal, Munir; Häsler, Barbara (Frontiers in Veterinary Science, 2020)
The chicken industry of Pakistan is a major livestock sub-sector, playing a pivotal role in economic growth and rural development. This study aimed to characterize and map the structure of broiler and layer production systems, associated value chains, and chicken disease management in Pakistan. Qualitative data were collected in 23 key informant interviews and one focus group discussion on the types of production systems, inputs, outputs, value addition, stakeholder involvement, market dynamics and disease management. Quantitative data on proportions of commodity flows were also obtained. Value chain maps were generated to illustrate stakeholder groups and their linkages, as well as flows of birds and products. Thematic analysis was conducted to explain the functionality of the processes, governance and disease management. Two major chicken production systems were identified: 1) Environmentally-controlled production (97-98%) and 2) Open house production (2-3%). The management systems for broilers were classified as I) Independent broiler production; II) Partially integrated broiler production; and III) Fully integrated broiler production, accounting for 65-75%, 16-20% and 10-15% of commercial broiler meat supply, respectively. The management systems for layers were classified as I) Partially integrated layer production and II) Independent layer production, accounting for 10% and 80-85% in the commercial egg production, respectively. The share of backyard farming for meat and eggs was 10-15%. All production systems could be categorised in terms of value chain management, dominance of actors, type of finished product and target customers involved. Numerous informal chains were identified in independent and partially integrated systems, with middlemen playing a key role in the distribution of finished products. Structural deficiencies in terms of poor farm management, lack of regulations for ensuring good farming practices and price fixing of products were key themes identified. Both private and public stakeholders were found to have essential roles in avian influenza passive surveillance, strategy development and provision of health consultancies. This study provides a foundation for policy-makers and stakeholders to investigate disease transmission, its impact and control. The structural and regulatory deficiencies identified could inform interventions to improve performance of the poultry sector to help meet growing chicken meat and egg demand in Pakistan.